2015
DOI: 10.1007/s11095-014-1593-y
|View full text |Cite
|
Sign up to set email alerts
|

Exosome Delivered Anticancer Drugs Across the Blood-Brain Barrier for Brain Cancer Therapy in Danio Rerio

Abstract: Purpose The blood–brain barrier (BBB) essentially restricts therapeutic drugs from entering into the brain. This study tests the hypothesis that brain endothelial cell derived exosomes can deliver anticancer drug across the BBB for the treatment of brain cancer in a zebrafish (Danio rerio) model. Materials and Methods Four types of exosomes were isolated from brain cell culture media and characterized by particle size, morphology, total protein, and transmembrane protein markers. Transport mechanism, cell up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
596
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 834 publications
(604 citation statements)
references
References 35 publications
6
596
1
1
Order By: Relevance
“…93 In 2014, Pascucci et al showed that Mesenchymal Stem Cells (MSC) could incorporate and deliver Paclitaxel to recipient cells through exosomes with increased anti-tumor effects. 94 This study suggests that MSC-derived exosomes could be a new strategy for drug delivery in cancer treatment.…”
Section: Exosomes As Drug Delivery Cargosmentioning
confidence: 99%
“…93 In 2014, Pascucci et al showed that Mesenchymal Stem Cells (MSC) could incorporate and deliver Paclitaxel to recipient cells through exosomes with increased anti-tumor effects. 94 This study suggests that MSC-derived exosomes could be a new strategy for drug delivery in cancer treatment.…”
Section: Exosomes As Drug Delivery Cargosmentioning
confidence: 99%
“…For hydrophobic membrane-permeable molecules, simple co-incubation at ambient or elevated temperature are often sufficient to load EVs [131,174]. Indeed, EVs derived from EL4 cells incubated with curcumin at room temperature were, after intranasal delivery, able to significantly delay brain tumor growth in the GL26 mice tumor model [137].…”
Section: Loading Evs With a Therapeutic Cargomentioning
confidence: 99%
“…Indeed, when comparing both loading strategies for paclitaxel, the post-formation method yields ~21 mg/g EV [175] and ~7.3 mg/g EV [131] compared to ~2 µg/g EV [152] for the pre-formation method. Overall, loading hydrophobic small molecules in EVs is more straightforward and efficient.…”
Section: Loading Evs With a Therapeutic Cargomentioning
confidence: 99%
“…62 In this search for novel therapeutic approaches, systemic injection of brain endothelial cell-derived EVs loaded with cytotoxic drugs (doxorubicin and paclitaxel) were demonstrated to cross the blood brain barrier in a fish model for GBM. 63 In addition, the expression of GBM-specific multidrug transporter could be reduced by anti-miR strategy introduced into exosome-producing donor cells. 64 Thus, cellular exosomes can be manipulated to specifically reach brain tissues, normally protected against xenobiotic invasion by the blood brain barrier (Fig.…”
Section: Could Evs Be Used As Drug Delivery Agents?mentioning
confidence: 99%